The pacing differences in performance levels of marathon and half-marathon runners - Ristanović, Ljubica; Cuk, Ivan; Villiger, Elias; Stojiljković, Stanimir; Nikolaidis, Pantelis T.; Weiss, Katja; Knechtle, Beat (Frontiers in Psychology, 2023)
Introduction: Many studies indicate a considerable impact of optimal pacing on long-distance running performance. Given that the amount of carbohydrates in metabolic processes increases supralinearly with the running speed, we may observe differences between the pacing strategies of two long-distance races and different performance levels of runners. Accordingly, the present study aimed to examine the differences in pacing strategies between marathon and half-marathon races regarding the performance levels of runners. Methods: The official results and split times from a total of 208760 (marathon, N=75492; half-marathon, N=133268) finishers in the "Vienna City Marathon" between 2006 and 2018 were analyzed. The percentage of the average change of speed for each of the five segments (CS 1-5), as well as the absolute change of speed (ACS) were calculated. The CS 1-5 for the marathon are as follows: up to the 10 th km, 10 th -20 th km, 20 th -30 th km, 30 th -40 th km, and from the 40 th km to the 42.195km. For the half-marathon, the CS 1-5 are half of the marathon values. Four performance groups were created as quartiles of placement separately for sexes and races: high-level (HL), moderate to high-level (MHL), moderate to low-level (MLL), and low-level (LL). Results: Positive pacing strategies (i.e., decrease of speed) were observed in all performance groups of both sex and race. Across CS 1-5, significant main effects (p<0.001) were observed for the segment, performance level, and their interaction in both sex and race groups. All LL groups demonstrated higher ACS (men 7.9% and 6.05%, as well as women 5.83% and 5.49%, in marathon and halfmarathon, respectively), while the HL performance group showed significantly lower ACS (men 4.14% and 2.97%, as well as women 3.16% and 2.77%, in marathon and half-marathon, respectively). Significant main effects (p<0.001) for the race were observed but with a low effect size in women (ŋ 2 =0.001). Discussion: Better runners showed more even pacing than slower runners. The halfmarathoners showed more even pacing than the marathoners across all performance groups but with a trivial practical significance in women.